Pain scores in torus fractures: Using text messages as an outcome collection tool. (February 2020) - Widnall, James; Capstick, Thomas; Wijesekera, Maheshi; Messahel, Shrouk; Perry, Daniel C.
Abstract : Aims: This study sought to estimate the clinical outcomes and describe the nationwide variation in practice, as part of the feasibility workup for a National Institute for Health and Care Excellence (NICE) recommended randomized clinical trial to determine the optimal treatment of torus fractures of the distal radius in children. Methods: Prospective data collection on torus fractures presenting to our emergency department. Patient consent and study information, including a copy of the Wong-Baker Faces pain score, was issued at the first patient contact. An automated text message service recorded pain scores at days 0, 3, 7, 21, and 42 postinjury. A cross-sectional survey of current accident and emergency practice in the UK was also undertaken to gauge current practice following the publication of NICE guidance. Results: In all, 30 patients with a mean age of 8.9 years were enrolled over a six-week period. Of the 150 potential data points, data was captured in 146, making the data 97.3% complete. Pain scores were recorded at day 0 (mean 6.5 (95% confidence interval (CI) 5.7 to 7.3)), day 3 (4.4 (95% CI 3.5 to 5.2)), day 7 (3.0 (95% CI 2.3 to 3.6)), day 21 (1.2 (95% CI 0.7 to 1.7)) and day 42 (0.4 (95% CI 0.1 to 0.7)). Of the 100 units who participated in the nationwide survey, 38% were unaware of any local or national protocols regarding torus fractures, 41% treated torus fractures with cast immobilization, and over 60% of patients had follow-up arranged, both contradictory to national guidelines. Conclusion: We have demonstrated the severity, recovery trajectory, and variation in pain scores among children with torus fractures. We demonstrate excellent follow-up of patient outcomes using text messages. Despite national guidelines, there is significant variation in practice. This data directly informed the development of an ongoing nationwide randomized clinical trial – the FORearm Fracture Recovery in Children Evaluation (FORCE) study.